Multicultural Learning and Teaching (De Gruyter, 2006)
Multicultural Learning and Teaching is a multidisciplinary, peer-reviewed international journal devoted to the education of people with diverse multicultural life experiences and backgrounds. Emphasis is on the interpretation of research literature, as well as recommendations for the improvement of the practice of multicultural education.